Pengaruh Kualitas Produk Dan Inovasi Produk Terhadap Kepuasan Konsumen Pada Umkm Di Kecamatan Klojen Kota Malang - Djoko Prasetyo Meinarto Djoko; Khamdan Suriyok; Ninik Churniawati (Institut Teknologi dan Bisnis Yadika, 2026)
This study aims to analyze the effect of product quality and product innovation on consumer satisfaction in MSMEs in Klojen District, Malang City. This study uses a quantitative approach with descriptive and associative methods. The research data was obtained by distributing questionnaires to 82 respondents who were consumers who had purchased MSME products in the area. The data analysis techniques used include validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, coefficient of determination, and hypothesis testing using F and t tests. The results show that product quality and product innovation simultaneously have a significant effect on customer satisfaction. Partially, product quality has a positive and significant effect on consumer satisfaction, while product innovation has no significant effect. The product quality variable is the most dominant factor in influencing consumer satisfaction. The coefficient of determination value shows that 31.1% of consumer satisfaction variation can be explained by product quality and product innovation, while the rest is influenced by other factors outside the scope of this study. The results of this study indicate that improving product quality is an important strategy for MSMEs in increasing consumer satisfaction